Efeitos da amiodarona na fase aguda da doença de Chagas experimental em camundongos - CASTILHO, Alessandra de (2016)
Chagas disease is caused by the protozoan Trypanosoma cruzi and affects approximately 7 million people throughout the world. During acute phase of infection, 60-70% of patients are asymptomatic, among them 25-30% will develop cardiomyopathy. Within the drugs used to treat Chagas disease, benznidazol is the most used in Brazil. Treatment is given for long periods, patients present several side effects, and the therapy presents variable efficacy in chronic phase. Thus, it is clear the necessity for new therapeutic approaches. Amiodarone, which has antiarrhythmic action in the chronic phase of the disease, has also shown in vitro trypanocidal effects. Our study aimed to evaluate the effects of this drug during acute phase of experimental Chagas disease in Balb/c mice infected with the Y strain of T. cruzi. Mice were treated for 20 days during the acute phase of the infection and the electrocardiogram (ECG) was performed on days 0 and 21 post infection. After euthanasia, heart fragments were collected for histopathologic analysis and to identify the presence of T. cruzi kDNA by specific PCR. The LSSP-PCR technique was used to detect differences in the genetic signatures of the parasite in both treated and untreated mice. By analyzing the curve, the peak of blood parasitism and the area under the curve, no differences were detected between treated and untreated mice (26.8 ± 4.1milions/mL.day versus 38.3±8.3milions/mL.day, respectively, p=0.232). However, treated mice had ECGs with improved QRS duration when compared to the untreated group (10.78 ± 0.49ms versus 12.82 ± 0.59ms, respectively, p=0.020). Histopathological analysis of heart showed the presence of inflammatory infiltrate in the atrium, ventricle and epicardium. The latter showed a reduction in the inflammatory infiltrate in mice treated with amiodarone. The LSSPPCR technique showed a distinctive gene signature of the parasite in the heart of treated and untreated mice. In conclusion, despite of amiodarone seems not to have a direct effect towards blood parasitism, this drug prevented the worsening of electrocardiographic and histopathologic parameters in the acute phase of experimental infection in mice. Our results reinforce the potential of this drug as an alternative therapy for Chagas disease during acute phase.